Hukum Tata Negara Dalam Perspektif Filsafat Islam - Irsal Irsal (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2023)
Abstract: This article discusses changes in Islamic law in the Indonesian constitutional context, including issues regarding the position and existence of Islamic law in the constitutional structure. by considering various social phenomena and facts that occur in society when carrying out actions and actions in accordance with the law. Due to historical facts and Indonesia's long history, Islamic law is an integral part of its journey. Since Indonesia gained independence on August 17 1945, a new era began in Indonesia's legal system. This legal system differentiates colonial law from national law. Because the national legal system does not completely depend on customary law, Islamic law, or Western law, there are many disputes and debates. Consequently, the constitution is an attempt to change something that already exists into something new by incorporating changes and adjustments. The process or effort to transform Islamic law into a national legal system aims to implement normative Islamic law into positive Islamic law, or what is often called positivism of Islamic law into the Indonesian legal system. The relationship between state, law and religion is balanced from a constitutional perspective. In the circle, religion is the most important component, as shown by the fact that the divine principle is the first principle in Pancasila. The following principles are the fiqh foundation for Islamic law: tauhidullah, insaniyah, tasamuh, ta'awun, silaturahim bain annas, justice, and benefit. Keywords: Law, Constitution, Islamic Philosophy